The geologic history of marine dissolved organic carbon from iron oxides - Nir Galili; Stefano M. Bernasconi; Alon Nissan; Uria Alcolombri; Giorgia Aquila; Marcella Di Bella; Thomas M. Blattmann; Negar Haghipour; Francesco Italiano; Madalina Jaggi; Ifat Kaplan-Ashiri; Kang Soo Lee; et al. (Nature, 2025)
Abstract Dissolved organic carbon (DOC) is the largest reduced carbon reservoir in modern oceans1,2. Its dynamics regulate marine communities and atmospheric CO2 levels3,4, whereas 13C compositions track ecosystem structure and autotrophic metabolism5. However, the geologic history of marine DOC remains largely unconstrained6,7, limiting our ability to mechanistically reconstruct coupled ecological and biogeochemical evolution. Here we develop and validate a direct proxy for past DOC signatures using co-precipitated organic carbon in iron ooids. We apply this to 26 marine iron ooid-containing formations deposited over the past 1,650 million years to generate a data-based reconstruction of marine DOC signals since the Palaeoproterozoic. Our predicted DOC concentrations were near modern levels in the Palaeoproterozoic, then decreased by 90−99% in the Neoproterozoic before sharply rising in the Cambrian. We interpret these dynamics to reflect three distinct states. The occurrence of mostly small, single-celled organisms combined with severely hypoxic deep oceans, followed by larger, more complex organisms and little change in ocean oxygenation and finally continued organism growth and a transition to fully oxygenated oceans8,9. Furthermore, modern DOC is 13C-enriched relative to the Proterozoic, possibly because of changing autotrophic carbon-isotope fractionation driven by biological innovation. Our findings reflect connections between the carbon cycle, ocean oxygenation and the evolution of complex life.